The future of health-care delivery [ why it must change and how it will affect you - Schimpff, Stephen C. , 1941- (Potomac Books, 2012)
Approximately 100,000 deaths per year in the United States result from preventable medical errors. This title explains why our health-care delivery system serves us so poorly, why it costs so much, and why government policy over many decades has not only failed to improve care delivery but has actually made it worse